Ethical issues of human enhancements for space missions to Mars and beyond. (January 2020) - Szocik, Konrad; Wójtowicz, Tomasz; Boone Rappaport, Margaret; Corbally, Christopher
Highlights: The concept of human enhancement is an ethical issue on Earth. Enhancement procedures can be considered as countermeasures in space. There are good reasons to accept human enhancement for space under special conditions. Abstract: A human mission to Mars is planned by public and private agencies. It is broadly discussed and studied by scientists in such fields as medicine and aerospace engineering. Less attention is being paid by philosophers and ethicists, and social scientists as well. The aim of this paper is to discuss possible ethical challenges and issues, which may appear during a human mission to Mars. We focus our attention mostly on one issue – the idea of human enhancements for space missions. While our case study is mostly a mission to Mars, ethical issues around human enhancement for space are also relevant for other longer-term human expeditions, including Lunar missions, and beyond. Because the space environment is hazardous for humans, it can be expected that new ethical issues concerning the value of human life may appear.